Osseus metaplasia in chronic renal allograft rejection - Makhoba, Aubrey M; du Toit-Prinsloo, Lorraine (African Journal of Nephrology, 2017)
The formation of heterotopic bone tissue outside the skeleton, known as osseous metaplasia, is a well-known phenomenon, but only a handful of cases describe this in renal allografts. We report the case of a 26-year-old female who was admitted to hospital for repair of an arteriovenous fistula of the right arm. Following her demise, the incidental finding of osseous metaplasia in the allograft kidney was made at autopsy. The pathophysiology, histology and possible clinical significance of the lesion are described.